Okay what’s the question ?
21 is the answer.You distribute 6 into the parentheses and you substitute 3 for x so 6(3-1)+9= f(x)=18-6+9 you add all the like terms and the answer is 21
The first integer (x) is equal to the consecutive even integers, x+2, x+4.
x = (x+2) + (x+4)
x = 2x + 6
x - 6 = 2x
x = -6 (First integer)
+2
-4 (Second integer)
+4
-2 (Third integer)
Integers: -6, -4, -2
Equation: x = (x+2) + (x+4)
Answer:
f(6) = 1
Step-by-step explanation:
Function:
f(x) = -2/3x + 5
f(6) = -2/3(6) + 5
f(6) = -4 + 5
f(6) = 1
Answer:
Step-by-step explanation:
We will use following steps to measure exactly 4 gallons of water with the help of 5 gallons and 3 gallons empty jugs.
1). Fill 3 gallons jug completely.
2). Pour this 3 gallons of water into 5 gallons jug. Now we have 3 gallons of water in 5 gallons jug and 3 gallons jug empty.
We can add 2 gallons of water in the empty space of 5 gallons jug more.
3). Fill the 3 gallons jug with the water again.
4). Pour this water into 5 gallons jug which can hold 2 gallons of water more.
Now we have 5 gallons of jug filled fully and 1 gallon water remaining in the 3 gallons jug.
5). Empty the 5 gallons jug completely.
6). Pour the remaining 1 gallon of remaining water in 3 gallons jug into 5 gallons jug.
7). Fill the 3 gallons jug completely and pour it into 5 gallon jug.
8). Finally we have 4 gallons of water in the 5 gallons jug.